An Analysis of Vehicle Vibration with Uncertain System Parameters - Milan Saga; Milan Letrich; Roman Kocur (Communications - Scientific letters of the University of Zilina, 2005)
The study proposes an application of fuzzy arithmetic for analysis of randomly excited structures with uncertain or inexact system parameters. The purpose of the paper is to investigate possibilities of a fuzzy technique in a vehicle dynamic analysis. The solution of the problem will be realised in MATLAB using the program CAR_FUZ.M with a special module INTLAB.